The Formation of the Key Assets of Human Capital at the Corporate Level - Boychenko, V. (Економічний вісник Донбасу, 2015)
The article is devoted to research of features of formation of key assets human capital at the corporate level and developing recommendations to improve the system development and professional development of staff. In the study proved that at the present stage one of the modern tools of personnel management is the evaluation of personnel based on the competency model, which will give the company a more efficient way to manage the following processes: achievement of strategic goals; selection of personnel; evaluation of personnel; the development of corporate culture; employee training; employee development; work with the personnel reserve. It is established that the development and implementation in industrial enterprises the proposed model of core competencies and development system and professional development staff will identify and justify the methodological guidance of the process of formation and development of the frames, to compare the size of the budget with identified needs, to establish priorities for professional learning that will enhance productivity, increase employee satisfaction with various aspects of the employment environment, enhance corporate culture. Стаття присвячена дослідженню особливостей формування ключових активів людського капіталу на корпоративному рівні і розробці рекомендацій щодо вдосконалення системи розвитку і підвищення професійної кваліфікації персоналу. В ході дослідження обґрунтовано, що на сучасному етапі одним із сучасних важелів управління персоналом є оцінка персоналу на основі моделі компетенцій, використання якої дасть підприємству можливість більш ефективного управління такими процесами: досягнення стратегічних цілей; підбір персоналу; оцінка персоналу; розвиток корпоративної культури; навчання співробітників; розвиток співробітників; робота з кадровим резервом. Встановлено, що розробка і впровадження на промислових підприємствах запропонованої моделі ключових компетенцій та системи розвитку і підвищення професійної кваліфікації персоналу дозволить виявити і обґрунтувати методологічні орієнтири процесу становлення і розвитку кадрів, зіставляти розмір бюджету з виявленими потребами, встановлювати пріоритети в професійному навчанні, що сприятиме підвищенню продуктивності праці, зростанню задоволеності персоналу різними аспектами трудової діяльності, підвищенню корпоративної культури. Статья посвящена исследованию особенностей формирования ключевых активов человеческого капитала на корпоративном уровне и разработке рекомендаций по совершенствованию системы развития и повышения профессиональной квалификации персонала. В ходе исследования обосновано, что на современном этапе одним из современных рычагов управления персоналом является оценка персонала на основе модели компетенций, использование которой даст предприятию возможность более эффективного управления следующими процессами: достижение стратегических целей; подбор персонала; оценка персонала; развитие корпоративной культуры; обучение сотрудников; развитие сотрудников; работа с кадровым резервом. Установлено, что разработка и внедрение на промышленных предприятиях предложенной модели ключевых компетенций и системы развития и повышения профессиональной квалификации персонала позволит выявить и обосновать методологические ориентиры процесса становления и развития кадров, сопоставлять размер бюджета с выявленными потребностями, устанавливать приоритеты в профессиональном обучении, что будет способствовать повышению производительности труда, росту удовлетворенности персонала различными аспектами трудовой деятельности, повышению корпоративной культуры.